Pendampingan Pembuatan Google Maps bagi UMKM sebagai Sarana Promosi di Desa Kedungbako - Pramita Sukma Wardani; Yeti Diah Wiyanti (Pakis Journal Institute, 2026)
This community service activity is motivated by the low level of digital technology utilization among Micro, Small, and Medium Enterprises (MSMEs), particularly in terms of promotion and online business location mapping. The purpose of this activity is to provide assistance to MSME actors in Kedungbako Village in creating and managing Google Maps as a digital promotional tool. The methods used include socialization, training, and direct mentoring through a participatory approach and hands-on training. The activity began with observation and identification of participants’ needs, followed by training on creating Google accounts, registering business locations, and managing business profiles. The results show that approximately 80% of participants successfully created and registered their businesses on Google Maps and were able to manage their business information independently. In addition, there was an increase in participants’ understanding of the importance of business digitalization and the use of digital platforms to expand market reach. This activity has a positive impact on improving the digital literacy of MSME actors and enhancing business visibility in the digital era. Therefore, this assistance is expected to support the strengthening of MSME competitiveness at both local and broader levels.